SUMOylation of Csk Negatively Modulates its Tumor Suppressor Function - Nan Cui (Neoplasia: An International Journal for Oncology Research, 2019)
Csk, a non-receptor tyrosine kinase, serves as an indispensable negative regulator of the Src family kinases (SFKs). However, little is known about regulation of Csk expression so far. SUMOylation, a reversible post-translational modification, has been shown to regulate many biological processes especially in tumor progression. Here we report that Csk is covalently modified by SUMO1 at lysine 53 (K53) both in vitro and in vivo. Treatment with hydrogen peroxide inhibited this modification to a certain extent, but PIAS3, identified as the main specific SUMO E3 ligase for Csk, could significantly enhance SUMO1-Csk level. In addition, phosphorylation at Ser364, the active site in Csk, had no effect on this modification. Ectopic expression of SUMO-defective mutant, Csk K53R, inhibited tumor cell growth more potentially than Csk wild-type. Consistent with the biological phenotype, the SUMO modification of Csk impaired its activity to interact with Cbp (Csk binding protein) leading to decreased c-Src phosphorylation at Y527. Our results suggest that SUMOylation of Csk mainly at lysine 53 negatively modulates its tumor suppressor function by reducing its binding with Cbp and consequently, inducing c-Src activation.